MODELING THE STRUCTURE OF WORD AND SENTENCE FORMATION IN THE UZBEK LANGUAGE USING MATHEMATICAL-NUMERICAL METHODS, PARTICULARLY LINEAR ALGEBRA TECHNIQUES SUCH AS THE GAUSSIAN METHOD (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article pertains to the fields of formal language modeling in linguistics, computational linguistics, NLP, and structural linguistics, and provides a description of the application of numerical methods—specifically the Gaussian method—in word and sentence formation in the Uzbek language. This study focuses on modeling the structure of word and sentence formation in the Uzbek language using mathematical-numerical methods, with a particular emphasis on linear algebra techniques such as the Gaussian method. Uzbek, as an agglutinative Turkic language, exhibits rich morphological and syntactic patterns that lend themselves naturally to formal, quantitative modeling. Words are composed of morphemes—roots and affixes—whose combinations follow well-defined morphological rules, while sentence structures are governed by syntactic relationships among subjects, predicates, and objects.